College students : risk preferences and pregaming - Lara, María Inés; De Santis, Mariana Olga; Carrazana Rivera, Andrea; Castroff, Carolina Edith (2022)
Pre-gaming is a drinking practice performed before attending a social event where more alcohol may or may not be consumed (Borsari, Murphy, et al., 2007; Pedersen & LaBrie, 2007; White & Hingson, 2013; Zamboanga et al., 2011; Pilatti et al., 2018) and is highly prevalent among young adults. There is abundant literature linking pre-gaming to binge drinking and the negative consequences associated with alcohol consumption. Therefore, pregaming and the associated health risks are important public health issues. The aim of this research is to extend the scarce research on this issue in Argentina in three respects. First, we adopt a microeconomic approach to analyze students' decisions to participate in pre-gaming. Second, we identify students' preferences in relation to their tolerance to the risk of exposing their health to health-damaging behaviors and analyze their relationship with choice. Third, we used primary information collected from a survey of consumption habits carried out in the faculties of economic sciences of the UNC and UNCU. Using selected items we identify four classes or groups according to their risk preferences. Although more than 40% of the students pregame, belonging to the groups with a greater predisposition to risk is associated with a higher probability of attending pre-parting.